1976
DOI: 10.1093/infdis/133.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea Caused in Gnotobiotic Piglets by the Reovirus-Like Agent of Human Infantile Gastroenteritis

Abstract: One- to four-day-old gnotobiotic piglets were inoculated orally with a reovirus-like agent obtained from human infants with acute gastroenteritis. Diarrhea developed in the piglets two to seven days after inoculation and was reproduced for five serial passages in one sequence and for three passages in another. Nineteen of 21 inoculated piglets developed diarrhea; reovirus-like particles were observed in intestinal contents and/or fecal samples from 17 animals with illness and from two inoculated piglets that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
1

Year Published

1976
1976
2003
2003

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 25 publications
3
42
0
1
Order By: Relevance
“…All animals in the infected group were diseased, but perhaps not all were at the same stage of infection when studied 72 h after they had received the virus. The variations in symptoms in our animals accord with the reported variability of the response of piglets to HRV infection (11,26,27). In part, these apparent variations may be due to the variable distribution and extent of the infection in the gut.…”
Section: Resultssupporting
confidence: 86%
“…All animals in the infected group were diseased, but perhaps not all were at the same stage of infection when studied 72 h after they had received the virus. The variations in symptoms in our animals accord with the reported variability of the response of piglets to HRV infection (11,26,27). In part, these apparent variations may be due to the variable distribution and extent of the infection in the gut.…”
Section: Resultssupporting
confidence: 86%
“…The intestine from calf 2 was examined by scanning electron microscopy. Equipment, procedures and isolation units have been described [13].Source and early calf passages of the D strain of the viral agent have been described [8,19,201. The calves were inoculated orally 114) at 8-10 hours old when they were first fed milk.…”
mentioning
confidence: 99%
“…Immunofluorescence in the small intestinal lamina propria was not evaluated because of nonspecific staining of eosinophils. Indirect-immunofluorescence [ 19,201 on sections of distal small intestine from calf 3 was done with acute and convalescent-phase human infant serum and then by fluorescein-conjugated goat antiserum to human gamma-globulin (Antibodies, Inc., Davis, Calif.). Intestine and mesenteric lymph nodes for transmission electron microscopy were prepared as described (171.…”
mentioning
confidence: 99%
“…Investigations recently have been directed toward finding susceptible animal species to be used as animal models [6][7][8][9]. Such studies have revealed that the human reovirus-like (HRVL) agent may induce diarrhea in piglets, monkeys, and calves [6,7,9,10].…”
mentioning
confidence: 99%